Dekonstruksi Kebijakan Sistem Pemidanaan Pada Hukum Pajak Di Indonesia Terhadap Pertanggungjawaban Tindak Pidana Penggelapan Pajak Penghasilan Badan - Annika Rahmawati; Setiawan, Puguh Aji Hari; Hartana, Hartana (Innovative: Journal Of Social Science Research, 2024)
ABSTRACT The aim of this research is to refine and simplify legal policies in the Law on General Provisions an Tax Procedures which are in accordance with Pancasila values in technical terms and implementation in the application of law and sanctions of tax crimes. It can become a proposition and development in term of legal knowledge as well as arrangements in law enforcement. The government needs to pay attention to the values of justice in the punishment system for criminal acts of corporate income tax evasion. Which uphold the values of justice in accordance with the fifth principle of Pancasila which contains fundamental meaning as the goal of an Indonesian state which is physically and mentally equitable rule of law state. Thus, the desired legal objectives (ius constituendum) can be achieved. Key Word : tax planning, tax evasion, punishment system, criminal elements, criminal sanctions, criminal act, corporate income tax